Complications And Cosmetic Outcome In A Late Presenting Primary Hypospedia Repair In Paediatric Population - Mohsin Zaman, Muhammad Kamran Khan, Hinna Qayum, Muhammad Zohaib, Zulfiqar Saeed, Dayan Ur Rehman (Pakistan Journal of Medical & Health Sciences, 2024)
Objective: The evaluation of complications and cosmetic outcomes was undertaken in patients undergoing primary hypospadias repair who presented late beyond the typical childhood age range at a tertiary care centre in Pakistan. Methods: A prospective observational study was conducted at the Department of Paediatric urology ward institute of kidney diseases Peshawar from May 2023 to October 2023. A total of 60 patients aged 7 to 14 years with primary hypospadias were enrolled. Tubularized incised plate urethroplasty was performed in 34 patients staged Bracka repair in 16 patients and transverse preputial island flap urethroplasty in 10 patients. Postoperative complications were recorded and cosmetic outcomes were assessed using the Hypospadias Objective Scoring Evaluation system at twelve months. Multivariate logistic regression analysis was performed to identify independent predictors of complications. Results: Postoperative complications were observed in 22 patients representing an overall complication rate of 36.7 percent. Urethrocutaneous fistula was the most common complication identified in 12 patients followed by meatal stenosis in 6 patients and urethral stricture in 4 patients. The mean Hypospadias Objective Scoring Evaluation score for the entire cohort was 14.2 out of 16. Tubularized incised plate urethroplasty demonstrated the lowest complication rate of 29.4 percent and the highest cosmetic score of 15.1. Proximal hypospadias and glans width less than 13 millimeters were identified as independent predictors of postoperative complications with odds ratios of 3.2 and 2.8 respectively. Conclusion: Primary hypospadias repair in late-presenting patients aged 7 to 14 years was associated with acceptable complication rates and satisfactory cosmetic outcomes. Tubularized incised plate urethroplasty demonstrated superior results for appropriately selected patients. Proximal hypospadias and small glans width were identified as independent predictors of complications. Keywords: Hypospadias, Urethroplasty, Postoperative Complications, Urethrocutaneous Fistula, Cosmetic Outcome, Late Presentation